The development of a framework for clinical education programme of undergraduate nursing students in Ghana - Gilbert Ti-enkawol Nachinab; Susan Jennifer Armstrong (BMC, 2024)
Abstract Introduction Clinical education is an important aspect of the training of nursing students but it is faced with challenges in Ghana. The development of a framework will respond to the need for improvement in the quality of clinical nursing education. This study describes part of a larger study which culminated in the development of a framework for a clinical education programme for undergraduate nursing students in Ghana. The aim of the current study was to integrate findings from a scoping review and situational analysis to develop a framework for clinical education in nursing. Methods A sequential multimethod design approach was used to conduct the study. A scoping review on the practices that facilitate clinical nursing education and situational analysis were first conducted. The lessons learnt from the scoping review and the situational analysis provided the data matrix that was triangulated to develop the framework. The framework was developed using the model for clinical education developed by South African Nursing Education Stakeholders in consultation with experts in nursing education. An implementation plan was developed from the framework and evaluated using a Delphi technique. Findings The resulting framework indicates the need for effective communication and collaboration between nursing education institution and the service setting to ensure that there is a well-structured clinical placement, formal supervision system and effective clinical assessment of students. The framework also proposes that to ensure quality clinical nursing education there is the need for Nursing Education Institutions to implement innovative and cost-effective clinical teaching methods. Conclusion The framework spells out the functions of the various stakeholders in nursing education and how these can be integrated and implemented to enhance quality clinical nursing education. Effectiveness of the thematic areas of the framework will increase the quality of clinical nursing education.